2011
DOI: 10.1038/leu.2011.12
|View full text |Cite
|
Sign up to set email alerts
|

IGHV unmutated CLL B cells are more prone to spontaneous apoptosis and subject to environmental prosurvival signals than mutated CLL B cells

Abstract: Tumor cells in chronic lymphocytic leukemia (CLL) are more prone to apoptosis when cultured ex vivo, because they lack prosurvival signals furnished in vivo via B-cell receptor (BCR)-dependent and -independent pathways. This study compared the susceptibility of unmutated (UM) and mutated (M) CLL B cells to spontaneous apoptosis and prosurvival signals. UM CLL B cells showed a significantly higher rate of spontaneous apoptosis than M CLL B cells. Nuclear factor-kB (NF-kB) was rapidly inactivated, and B-cell leu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
41
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(52 citation statements)
references
References 47 publications
(49 reference statements)
10
41
1
Order By: Relevance
“…Overall, our data demonstrated that physical contact between CLL cells and the endothelium is essential to trigger the cellular secretion of several soluble factors mediating additional survival hits on leukemic cells. Furthermore, in agreement with recently reported results, 24 we observed that spontaneous apoptosis in vitro was higher in IGHV-unmutated CLL cells than in IGHV-mutated ones. When CLL cells were co-cultured on the endothelial layer, CLL survival was comparable in the two prognostic subsets.…”
Section: Discussionsupporting
confidence: 82%
“…Overall, our data demonstrated that physical contact between CLL cells and the endothelium is essential to trigger the cellular secretion of several soluble factors mediating additional survival hits on leukemic cells. Furthermore, in agreement with recently reported results, 24 we observed that spontaneous apoptosis in vitro was higher in IGHV-unmutated CLL cells than in IGHV-mutated ones. When CLL cells were co-cultured on the endothelial layer, CLL survival was comparable in the two prognostic subsets.…”
Section: Discussionsupporting
confidence: 82%
“…In particular, CLL cells from patients with aggressive disease typically respond with increased survival CLL cells from patients with indolent disease usually do not respond or may even respond by undergoing apoptosis. 4,8,43 In the case of TLR9 signaling, these distinct cellular responses have been associated with differences in intracellular signal transduction. 8,9,20,43 In particular, CpG-stimulated UM CLL cells exhibit greater and prolonged activation of several important downstream signaling molecules, including the transcription factor NF-kB and the kinases Akt, ERK and JNK.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, UM CLL cells have been recently found to respond more efficiently to microenvironmental pro-survival signals than mutated (M) CLL cells, being on the other hand more susceptible to spontaneous apoptosis when these signals are absent. 4 Moreover, UM CLL cells frequently have high levels of the enzyme activation-induced cytidine deaminase and present evidence of ongoing class-switch recombination, both hallmarks of recent activation by microenvironmental signals. 5 Signals that are transmitted through Toll-like-receptor-9 (TLR9) may also have a role in CLL, as they could drive the expansion of CLL cells that express BCRs reactive with DNA or DNA-containing complexes.…”
Section: Introductionmentioning
confidence: 99%
“…The notion that ZAP-70 ϩ29 and unmutated CLL cells 20,56 are more responsive to BCR stimulation and other microenvironmental signals 28 suggests that patients with high-risk disease features may be particularly well suited for alternative treatments that target the microenvironment. Indeed, early clinical data from ongoing trials with the Btk inhibitor PCI-32765 57 and the PI3K inhibitor CAL-101 58 suggest that high-risk CLL patients respond well to these agents that disrupt CLL-microenvironment interactions.…”
Section: Bcr and Bcr-associated Kinases (Syk Btk And Pi3k Delta)mentioning
confidence: 99%
“…This is supported by the notion that GEPs of CLL cells after NLC coculture 13 are strikingly similar to GEPs of CLL cells isolated from secondary lymphatic tissues, 14 which show signs of BCR and NF-B activation and up-regulation of BCR target genes such as CCL3 and CCL4. 13,14 The diverse molecular mechanisms of CLL-NLC cross-talk have been extensively studied, [10][11][12][13][15][16][17][18][19][20] and have revealed important pathways and therapeutic targets of CLL-microenvironment cross-talk. For example, NLCs express CXCL12, 21 CXCL13, 12 CD31, plexin B1, 16 BAFF, APRIL, 15 and vimentin.…”
Section: Nlcsmentioning
confidence: 99%